An uncommon diagnosis behind a common respiratory symptom: Lobular capillary hemangioma of the trachea in a pediatric patient - Alireza Eshghi; Mohammad Hadi Akbarizadeh mashkani; Mohammad sharifi; Nasrin hoseiny nejad; Behnoosh Tasharrofi; Elham Zarei (Radiology Case Reports, 2025)
Lobular capillary hemangioma (LCH) is a benign vascular tumor that is usually found in the skin and mucous membranes. However, tracheal LCH is rare and presents with non-specific respiratory symptoms such as chronic cough, hemoptysis or airway obstruction, which often lead to misdiagnosis. This case report describes a six-year-old girl who was initially misdiagnosed with hyperreactive airway disorder due to persistent coughing and respiratory distress. Further evaluation via CT scan and bronchoscopy revealed a tracheal mass, which was confirmed as LCH following histopathological analysis. Successful treatment involved an excisional biopsy, which resolved the symptoms. This case highlights the importance of considering tracheal masses such as LCH in pediatric patients presenting with refractory respiratory symptoms and emphasizes the need for advanced imaging and endoscopy techniques to ensure accurate diagnosis and effective management.